Temporal bone primary inverted papilloma – Case Report and review of the literature - Avallone, Emilio; Raab, Peter; Lenarz, Thomas; Willenborg, Kerstin Marion (Laryngo-Rhino-Otologie, 2021)
Inverted papilloma of middle ear is an extremely rare lesion of the respiratory epithelium that normally occurs in the nasal cavity and paranasal sinuses. So far less than 17 cases were described in literature. A 45-year-old patient was admitted in our Department with hearing loss, otorrhea and pulsing tinnitus on the right ear. The clinical examination showed a granulation tissue on the right eardrum. No tumor formation was seen in the nasal cavity. The MRI showed a tissue formation in the tympanic cavity with an extension in the middle cranial fossa. A mastoidectomy with antrotomy and duraplasty was performed. The histological diagnosis was inverted papilloma of the middle ear. In a second step occurred an eradication of the tumor with a subtotal petrosectomy. The etiology of the inverted papilloma of the middle ear is unknown. Our case is so far the 18nd case described.Our experience has shown that the eradication of the tumor with a subtotal petrosectomy resulted as reasonable procedure. A long-term follow-up is suggested in order to detect possible recurrence or malignant transformation.
Keywords: otologie; skullbase; middle ear; inverted papillom; Schädelbasis; Mittelohr; invertiertes Papillom; Schädelbasischirurgie